2006
DOI: 10.1902/jop.2006.060016
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Crevicular Fluid Osteopontin Levels in Periodontal Health and Disease

Abstract: OPN levels increase in GCF from healthy to periodontitis states, and periodontal treatment results in the reduction of OPN levels. The data indicate that OPN may play a key role in, and could be considered a biomarker of, periodontal disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 22 publications
(29 reference statements)
4
37
0
Order By: Relevance
“…The increased recognition of the interactions between the cells of the immune and skeletal system has led to the seeking of a variety of regulatory molecules that play a role in the progression of periodontal disease [25][26][27]. In previous studies, the bestknown markers of the bone turnover have been widely investigated in GCF samples of patients with different periodontal diseases and implicated to be associated with the progression of periodontal diseases [28][29][30]. Several investigations provided contradictory evidence about the role of osteocalcin in GCF of patients with periodontitis [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The increased recognition of the interactions between the cells of the immune and skeletal system has led to the seeking of a variety of regulatory molecules that play a role in the progression of periodontal disease [25][26][27]. In previous studies, the bestknown markers of the bone turnover have been widely investigated in GCF samples of patients with different periodontal diseases and implicated to be associated with the progression of periodontal diseases [28][29][30]. Several investigations provided contradictory evidence about the role of osteocalcin in GCF of patients with periodontitis [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…OPN, is mainly involved in enhancing osteoclastic action and has also been detected in GCF in some aforementioned studies. 24,25 The effects of initial periodontal therapy also confirmed that OPN levels significantly decreased and were correlated with decreasing clinical periodontal parameters. 25 Kido et al reported that OPN in GCF may be considered as a marker of alveolar bone loss in periodontitis, while Sharma and Pradeep reported that GCF OPN levels were higher in periodontitis patients compared to those with gingivitis and healthy subjects.…”
mentioning
confidence: 74%
“…24,25 The effects of initial periodontal therapy also confirmed that OPN levels significantly decreased and were correlated with decreasing clinical periodontal parameters. 25 Kido et al reported that OPN in GCF may be considered as a marker of alveolar bone loss in periodontitis, while Sharma and Pradeep reported that GCF OPN levels were higher in periodontitis patients compared to those with gingivitis and healthy subjects. 24,25 Conversely, the present study showed similar total amounts of OPN GCF levels in all geriatric groups.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Several investigations on OPN indicated that OPN concentrations in gingival crevicular fluid increased proportionally with the progression of disease; and OPN levels in GCF were significantly reduced following nonsurgical periodontal treatment (33,34).…”
Section: Markers Of Alveolar Bone Lossmentioning
confidence: 99%